Epigallocatechin-3-gallate decreases the transport and metabolism of simvastatin in rats. (2nd January 2017) - Yang, Wei; Zhang, Qiuyang; Yang, Yue; Xu, Jiaqiu; Fan, Ali; Yang, Chung S.; Li, Ning; Lu, Yang; Chen, Jiayin; Zhao, Di; Aa, Jiye; Chen, Xijing
Abstract: 1. This study aimed to investigate the potential impact of epigallocatechin-3-gallate (EGCG) on the pharmacokinetic behaviors of simvastatin and its metabolite simvastatin acid and explored the possible role of metabolizing enzymes and transporters of this food–drug interaction. 2. Female SD rats were intravenously administered with EGCG (5 mg/kg), ketoconazole (10 mg/kg) and rifampin (10 mg/kg), followed by intravenous administration of 2 mg/kg simvastatin. In vitro, the effects of EGCG on Cytochrome P450 enzymes (CYP450) and organic anion transporting polypeptides (OATPs) were studied using human hepatic microsomes and human embryonic kidney 293 (HEK293) cells overexpressing OATP1B1 or OATP1B3. The results showed that areas under concentration–time (AUC) curves of simvastatin and simvastatin acid increased by 2.21- and 1.4-fold while the clearance was reduced by 2.29- and 1.4-fold, respectively, when co-administered with EGCG. In vitro experiments suggested the inhibitory effect of EGCG on CYP enzymes (IC50 : 18.37 ± 1.36 μM, 26.08 ± 1.51 μM for simvastatin and simvastatin acid, respectively). Simvastatin transport by OATP1B1 and OATP1B3 was also inhibited by EGCG (IC50 : 8.68 ± 1.27 μM and 22.67 ± 1.42 μM, respectively). 3. The presently reported novel food–drug interaction between EGCG and simvastatin involves the inhibition of not only CYP450 enzymes but also OATPs by EGCG.